Leadership management in the management of islamic educational institutions - Putra Mahendra Gunawan Nasution (Enrichment : Journal of Management, 2023)
The purpose of this study is to clarify research on the role of leadership management in the management of Islamic educational institutions. This research uses a qualitative method with a descriptive approach by processing literature, literature study which means as a series of activities related to the method of collecting library information, reading, and storing in the processing of research materials. The results of this study show that the leader is someone who is able to influence the attitudes and deeds of his members in the workplace by using power in his activities that can be directed and influenced by the leader in relation to the tasks of his subordinates that must be carried out. A good leadership spirit is required to be possessed by the leader in order to create a good atmosphere in the management of Islamic educational institutions. The type of leadership applied in Islamic educational institutions greatly affects the success of Islamic educational institutions that are led and must be able to have good leadership competencies in order to work appropriately, fairly, and wisely.